Makna Kalimat Amr dan Nahy dalam Kitab Bidāyat al-Hidāyah Karya Imam Al-Ghazālī - Puspita, Rani; Yusup, Maulana (Alsina : Journal of Arabic Studies, 2023)
This article aims to explore various meanings within the sentences of "amr" (command) and "nahy" (prohibition) found in the book "Bidāyat al-Hidāyah". The research method employed is qualitative research. The data sources are divided into primary data sources, namely the book "Bidāyat al-Hidāyah," and secondary data sources, including various literature such as books, journals, and other texts related to the topics studied by the researcher. The data collection techniques used are documentation and purposive sampling. The sampling results indicate the presence of 14 sentences in the form of "fiʿil amr" (verbs of command), two sentences of "ism fiʿil amr" (nouns of command), and one sentence of " fiʿil muḍāri' " (present tense verb) preceded by "lam amr." As for "nahy", there are 12 sentence samples. The meanings of "amr" include ten sentences meaning guidance, one sentence meaning discipline, two sentences meaning pure command, two sentences meaning creation, and one sentence meaning prayer. Regarding the "nahy" sentences, four sentences were found to mean guidance, two sentences meant clarification of consequences, one sentence meant pure prohibition, one sentence meant admonition, one sentence meant avoidance, one sentence meant to dislike, and one sentence meant belittlement.